2020
DOI: 10.1029/2020jd033096
|View full text |Cite
|
Sign up to set email alerts
|

Black Carbon Emission and Wet Scavenging From Surface to the Top of Boundary Layer Over Beijing Region

Abstract: The heating impacts caused by black carbon (BC) may modify the atmospheric dynamics of planetary boundary layer (PBL), essentially determined by its vertical distribution. In this study we performed simultaneous measurements of detailed BC properties at both surface (50 m) and mountain sites (1,344 m) over Beijing region. The latter represents the top of PBL and was influenced by surface anthropogenic emissions, particularly around midday when PBL was developed, allowing continuous investigations on the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…BC concentrations observed in rural Beijing and urban Spain both showed a seasonal variation of fall > winter > spring > summer, which was not the same as in rural Qingdao, most likely due to increased biomass burning during the harvest season [65]. As reported by previous studies, the seasonal variation of atmospheric BC could be driven by both emissions [32,33] and meteorological conditions [26,31]. These results indicate that the contribution of the sources of BC in rural Qingdao was uniquely seasonal, while the magnitude of the influence of meteorological factors (WS, WD, BLH, and precipitation) on BC varied between seasons.…”
Section: Seasonal Variationsmentioning
confidence: 68%
See 1 more Smart Citation
“…BC concentrations observed in rural Beijing and urban Spain both showed a seasonal variation of fall > winter > spring > summer, which was not the same as in rural Qingdao, most likely due to increased biomass burning during the harvest season [65]. As reported by previous studies, the seasonal variation of atmospheric BC could be driven by both emissions [32,33] and meteorological conditions [26,31]. These results indicate that the contribution of the sources of BC in rural Qingdao was uniquely seasonal, while the magnitude of the influence of meteorological factors (WS, WD, BLH, and precipitation) on BC varied between seasons.…”
Section: Seasonal Variationsmentioning
confidence: 68%
“…Regional transport can also enhance BC concentrations in urban and remote areas [29,30]. Typically BC is also subject to a reduction in concentration due to removal by wet deposition (rainfall and snowfall) [31]. The above results indicate that the variation of BC concentrations in different regions and the relative contribution of emission sources are influenced by geographical location, meteorological conditions, and source sector distributions.…”
Section: Introductionmentioning
confidence: 78%
“…The scavenging effect of TP on BC removal from the atmosphere has been well established. 61,62 However, it was excluded by the stepwise regression model, likely due to the collinearity with both RH and T. 63 For the MLR models using T, RH, and the four wind vectors, the average R 2 value for all grid cells was 0.44 ± 0.20. A similar dependence of BC concentrations on these meteorological factors has often been reported.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, significant correlations between BLH and T ( p = 0.01) and between BLH and RH ( p = 0.04) were found in this study and have been reported by other studies. , Although T and RH were also correlated significantly, they were not totally collinear, and R 2 values are reduced by 0.03 with one of them excluded. The scavenging effect of TP on BC removal from the atmosphere has been well established. , However, it was excluded by the stepwise regression model, likely due to the collinearity with both RH and T . For the MLR models using T, RH, and the four wind vectors, the average R 2 value for all grid cells was 0.44 ± 0.20.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As one of the most critical factors determining the absorption of BC, the mixing state of individual BC particles is highly complicated and constantly changing during their transport in the atmosphere. BC particles were observed to be extensively internally mixed worldwide (Adachi et al., 2016; Liu et al., 2017; Motos et al., 2019; Zhang et al., 2017), including various areas around China, such as the Pearl River Delta (PRD) region (Huang et al., 2012; Tan et al., 2016; Zhang et al., 2014), Yangtze River Delta region (Kleffmann & Wiesen, 2005), and North China Plain (D. Liu et al., 2020; Yu et al., 2020; Zhang et al., 2018), leading to significantly enhanced light scattering and absorption capacity of BC. While extensive studies have gained insight into the evolution of mixing state of BC particles, it has been merely linked to the condensation of secondary species, such as sulfate, nitrate, and organics (Ault et al., 2010; Cahill et al., 2012; Gaston et al., 2013; Yuan et al., 2019; Zhang et al., 2013, 2018).…”
Section: Introductionmentioning
confidence: 99%